Assessment of Hospital Anxiety and Depression Scale in Emergency Department in Iraq - Hanan N Najaf; Rusul F Hasan; Nidhal H Hammod; Samer A Hasan (Acta Medica Iranica)
Depression is a serious medical condition that affects a person’s feelings, thought, and how to behaves. It causes sadness, hopelessness, and helplessness, interfering with daily activities (1). Anxiety is a normal emotion that anyone experiences from time to time that range from mild to severe of worry or fear. The study's objective was to assess anxiety and depression in a sample of worker in an emergency Department worker in middle and south of Iraq. The workers in an emergency department in hospitals of middle and south of Iraq who deal with a lot of stress and under pressure most of day are sample of this study which designs to assess anxiety and depression in these workers, surely who accepted to participate in this study between Jan to May 2023 by using Hospital anxiety and depression scale (HADs) in Arabic was employed. The workers in an emergency department were more than half of them associated with significant anxiety and depression due to their works under pressure in hospitals. In conclusion, this study showed elevated risk of depression and anxiety among the emergency Department staff, and this elevated directly proportional to nature of work, Economic status, age and Level of education for worker.